POLA PEMBINAAN KEAGAMAAN PADA SISWA SEKOLAH LUAR BIASA PELITA HATI PEKANBARU - Sariah Sariah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Everyone needs education, because education is the foundation for life to acquire information and knowledge to develop themselves both in the family, school and community environments. As a child mentally retarded retarded retarded intelligence but still has the potential to be developed, the main characteristics of these children have a disadvantage in thinking and reasoning. The impact of the weakness is having the ability to learn and social adaptation in below the average normal children. The purpose of this study was to determine the formation of religious for the child at students of Extraordinary School Pelita Hati Pekanbaru, while the benefits are practically as information for managers, educators, coaches, as well as referrals to families and communities who have children with intellectual challenges in developing the potential of children, especially religious values which constitute the basic provision in this life, and the theoretical results of this study are expected later obtain information that can be used as a coaching principles concerning religious values in students retarded. Religious development patterns conducted by the Extraordinary School Pelita Hati through the field of religious studies, science, PKN and commemorate the Day of the Religious, recitals by using props, concrete objects as a medium that is easily understood by students using transcendental pattern. With this pattern teacher is required to transform the science and give examples of various approaches and fostering student religious consciousness in mental retardation.